Evaluation of pharmacotherapy complexity in residents of long-term care facilities: a cross-sectional descriptive study - Vanessa Alves-Conceição; Daniel Tenório da Silva; Vanessa Lima de Santana; Edileide Guimarães dos Santos; Lincoln Marques Cavalcante Santos; Divaldo Pereira de Lyra (BMC, 2017)
Abstract Background Polypharmacy is a reality in long-term care facilities. However, number of medications used by the patient should not be the only predictor of a complex pharmacotherapy. Although the level of complexity of pharmacotherapy is considered an important factor that may lead to side effects, there are few studies in this field. The aim of this study was to evaluate the complexity of pharmacotherapy in residents of three long-term care facilities. Methods A cross-sectional study was performed to evaluate the complexity of pharmacotherapy using the protocols laid out in the Medication Regimen Complexity Index instrument in three long-term care facilities in northeastern Brazil. As a secondary result, potential drug interactions, potentially inappropriate medications, medication duplication, and polypharmacy were evaluated. After the assessment, the association among these variables and the Medication Regimen Complexity Index was performed. Results In this study, there was a higher prevalence of women (64.4%) with a high mean age among the study population of 81.8 (±9.7) years. The complexity of pharmacotherapy obtained a mean of 15.1 points (±9.8), with a minimum of 2 and a maximum of 59. The highest levels of complexity were associated with dose frequency, with a mean of 5.5 (±3.6), followed by additional instructions of use averaging 4.9 (±3.7) and by the dosage forms averaging 4.6 (±3.0). Conclusions The present study evaluated some factors that complicate the pharmacotherapy of geriatric patients. Although polypharmacy was implicated as a factor directly related to complexity, other indicators such as drug interactions, potentially inappropriate medications, and therapeutic duplication can also make the use of pharmacotherapy in such patients more difficult.